2015
DOI: 10.1111/wrr.12283
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical cues in orofacial tissue engineering and regenerative medicine

Abstract: Cleft lip and palate patients suffer from functional, aesthetical, and psychosocial problems due to suboptimal regeneration of skin, mucosa, and skeletal muscle after restorative cleft surgery. The field of tissue engineering and regenerative medicine (TE/RM) aims to restore the normal physiology of tissues and organs in conditions such as birth defects or after injury. A crucial factor in cell differentiation, tissue formation, and tissue function is mechanical strain. Regardless of this, mechanical cues are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 133 publications
(260 reference statements)
0
21
0
2
Order By: Relevance
“…Since a cleft palate is a large critical size defect that is influenced by strong masticatory forces [40], a stable and permanent bone substitute is essential that first enables a direct contact to mature bone and second promotes the formation of new bone produced naturally in the patient [18]. That is why the tissue engineering approach is very promising, even if the present study has shown a negative clinical result.…”
Section: Discussionmentioning
confidence: 85%
“…Since a cleft palate is a large critical size defect that is influenced by strong masticatory forces [40], a stable and permanent bone substitute is essential that first enables a direct contact to mature bone and second promotes the formation of new bone produced naturally in the patient [18]. That is why the tissue engineering approach is very promising, even if the present study has shown a negative clinical result.…”
Section: Discussionmentioning
confidence: 85%
“…An accumulation of collagen type I and III fibers and other ECM proteins after injury results in a disorganized fiber structure and hypertrophic scar formation . Wound tension or mechanical stress is another causative factor for scar formation . The skin of the human face is maximally extensible perpendicular to relaxed skin tension lines, implying that tension is minimized when surgical incisions are created along these lines …”
Section: Cleft Surgery Can Results In Fibrosis and Scar Formationmentioning
confidence: 99%
“…65,66 Wound tension or mechanical stress is another causative factor for scar formation. 67,68 The skin of the human face is maximally extensible perpendicular to relaxed skin tension lines, implying that tension is minimized when surgical incisions are created along these lines. 67 Prolonged inflammation and oxidative stress blocks the remodeling phase and promotes excessive fibrosis and scarring.…”
Section: Cleft Surgery Can Results In Fibrosis and Scar Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery and other types of traumatic injury not only cause inflammatory injury, fibrosis, and scar formation (Brouwer et al, 2015), but are associated with the release of free heme (Wagener et al, 2003a). Heme is the prosthetic group of a number of physiologically important hemoproteins (e.g., hemoglobin, cytochromes or cyclooxygenase).…”
mentioning
confidence: 99%